VD_FINDINFO HC / 2010 / 647 vom 6. Dezember 2010 - VD Tribunal cantonal (2010)
MESURE DE CONTRAINTEDROIT DES ÉTRANGERS | 75 al. 1 let. g LEtr, 75 al. 1 let. h LEtr, 76 al. 1 let. b ch. 1 LEtr, 76 al. 1 let. b ch. 3 LEtr, 76 al. 1 let. b ch. 4 LEtr, 76 al. 4 LEtr, 80 al. 1 LEtr, 80 al. 6 LEtr, 30 LVLEtr, 31 LVLEtr